Primary School Literacy Program Management - Suhesti, Pancaria; Anwar, Syaiful; Yetri, Yetri (Universitas Islam Negeri Raden Intan Lampung, 2023)
Literacy can be acquired through the learning process through two literacy skills that students can acquire gradually, namely reading and writing. This research is motivated by the fact that there is no literacy program at elementary school 1 sukarame dua, teluk betung, Lampung, Indonesia that has been conceptualized by the school as it should be, then educators have not received training on literacy programs, there is no School Literacy Team (TLS), the availability of books in the library is relatively poor, both in terms of quantity and quality, including the absence of a comfortable reading room for school residents. This study aims to determine and analyze the management of the literacy program at State Elementary School I Sukarame Dua, West Teluk Betung Subdistrict, Bandar Lampung City, from the planning, implementation and evaluation stages. Based on the results of the study, it can be concluded that the literacy program at elementary school 1 sukarame dua, teluk betung, Lampung, Indonesia has an integration process of all school components, starting from the planning process, then the implementation process which has several stages, namely the habituation, learning and development stages. As a new program, the implementation of literacy at elementary school 1 sukarame dua, teluk betung, Lampung, Indonesia is seen as good by all school components. In addition, in the evaluation process, elementary school 1 sukarame dua, teluk betung, Lampung, Indonesia can provide the results of what are the inhibiting factors, namely the lack of books in the library, and the lack of awareness of students to read, some things that can be a solution to the results of the evaluation of the literacy program carried out, namely elementary school 1 sukarame dua, teluk betung, Lampung, Indonesia can provide a variety of new books, approach parents and each school component, especially homeroom teachers, provide reinforcement, enthusiasm and encouragement to students about reading books and always encourage and give prizes to students who diligently read books.